A new species of the deepwater scorpionfish genus Phenacoscorpius (Teleostei: Scorpaenidae) from the Galápagos Islands - Wibowo, Kunto; Motomura, Hiroyuki (Zootaxa, 2017)
A new species of scorpionfish, Phenacoscorpius mccoskeri, is described based on three specimens from the Galápagos Islands, Ecuador, eastern Pacific. The new species is distinguished from other species of Phenacoscorpius by the following combination of characters: 19–20 pectoral-fin rays, middle rays branched; 5–19 pored lateral-line scales; palatine teeth present; small slit behind fourth gill arch; second preopercular spine absent; and nuchal and parietal spines distinct; in addition to some morphometric characters, including head length and width, interorbital width, caudal-peduncle depth and postorbital length.